All Days 2011
DOI: 10.2118/140185-ms
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Microseismic Mapping and Complex Fracture Modeling to Characterize Fracture Complexity

Abstract: Microseismic mapping (MSM) has shown that the occurrence of complex fracture growth is much more common than initially anticipated and is becoming more prevalent with the increased development of unconventional reservoirs (shale-gas). The nature and degree of fracture complexity must be clearly understood to select the best stimulation design and completion strategy. Although MSM has provided significant insights into hydraulic fracture complexity, in many cases the interpretation of fracture growth has been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(53 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…Microseismic and nondestructive testing methods have been used to investigate the hydrofracturing crack morphologies [18][19][20][21][22]. The laboratory experiments show that the dip angle affects crossing behaviours between hydraulic and pre-existing fractures to form the complex fracture networks [23].…”
Section: Introductionmentioning
confidence: 99%
“…Microseismic and nondestructive testing methods have been used to investigate the hydrofracturing crack morphologies [18][19][20][21][22]. The laboratory experiments show that the dip angle affects crossing behaviours between hydraulic and pre-existing fractures to form the complex fracture networks [23].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Cipolla et al (2011) showed that dual porosity models are not adequate for simulating complex fracture patterns. They presented flow simulations indicating that neither early-time rate nor estimated ultimate recovery is captured by the dual porosity approach.…”
Section: Introductionmentioning
confidence: 99%
“…The multistage, multi-perforation clusters per fracturing treatment in a horizontal wellbore and the natural fractures may create a fracture network system that may enhance the stimulated reservoir volume (SRV) and improve both the initial production and the ultimate recovery factor (Mayerhofer et al 2008;Cipolla et al 2009). There are many factors which influence the fracture propagation, like the horizontal stress difference, density of natural fractures, injection rate, number of perforation clusters, and the spacing of clusters (Yost et al 1988;Palmer et al 2007;Cipolla et al 2011;Olson and Wu 2012).…”
Section: Introductionmentioning
confidence: 99%